Evaluation of the Effects of Doxapram in Combination with Xylazine on Recovery of Horses Isoflurane-Anesthetized - Midon, Monica [UNESP]; Yamada, Diego Iwao [UNESP]; Zangirolami Filho, Darcio [UNESP]; Natalini, Claudio Correa; Escobar, Andre [UNESP]; Clark-Price, Stuart Charles (Elsevier, 2022)
This randomized double-blinded study evaluated the recovery from isoflurane anesthesia in horses receiving doxapram and xylazine. 6 horses were anesthetized 4 times (minimum of 2-week washout period). Anesthesia was performed with xylazine (0.6 mg/kg), ketamine (2.2 mg/kg), midazolam (0.1 mg/kg), and maintained with isoflurane for 90 minutes. At recovery, horses received one of the following randomized treatments: RX: xylazine (0.2 mg/kg), RXD1: xylazine (0.2 mg/kg) and doxapram (0.1 mg/kg), RXD2: xylazine (0.2 mg/kg) and doxapram (0.2 mg/kg), or RS: saline. Recoveries were rope-assisted and evaluated with a descriptive qualitative scale. Heart rate, respiratory frequency (fR), and blood gas analysis were evaluated at 5 minutes intervals while the horse allowed. Data were analyzed with ANOVA or Friedman test (P <.05). Times to sternal (minutes) were RX: 40.5 ± 12.3, RXD1: 25.8 ± 11.5, RXD2: 31.4 ± 7.0, and RS: 33.4 ± 5.3, and were not different. Times to standing (minutes) were RX: 41.0 ± 9.9, RXD1: 33.5 ± 6.2, RXD2: 40.0 ± 11.3, and RS: 36.3 ± 9.9, and were not different. Heart rate decrease over time within RXD1 and RXD2 (T0 = 47 ± 15 and 47 ± 15, T5 = 38 ± 8 and 38 ± 8, T10 = 39 ± 4 and 36 ± 6, respectively), but was not different among groups. There was no difference in fR among groups or over time. There was no difference in recovery scores among groups. In conclusion, administration of doxapram to isoflurane-anesthetized horses did not change recovery time or quality.
Keywords: Alpha-adrenergic agonists; Anesthetic recovery; Doxapram; Equine; Inhalant anesthesia